Thermophilic biohydrogen production strategy using agro industrial wastes: Current update, challenges, and sustainable solutions. (November 2022) - Haque, Shafiul; Singh, Rajeev; Pal, Dan Bahadur; Faidah, Hani; Ashgar, Sami S.; Areeshi, Mohammed Y.; Almalki, Atiah H.; Verma, Bhawna; Srivastava, Neha; Gupta, Vijai Kumar
Abstract: Continuously increasing wastes management issues and the high demand of fuels to fulfill the current societal requirements is not satisfactory. In addition, severe environmental pollution caused by generated wastes and the massive consumption of fossil fuels are the main causes of global warming. In this scenario, production of hydrogen from organic wastes is a potential and one of the most feasible alternatives to resolve these issues. However, sensitivity of H2 production at higher temperature and lack of potential substrates are the main issues which are strongly associated with such kinds of biofuels. Therefore, the present review is targeted towards the evaluation and enhancement of thermophilic biohydrogen production using organic, cellulosic wastes as promising bioresources. This review discusses about the current status, development in the area of thermophilic biohydrogen production wherein organic wastes as key substrate are being employed. The combinations of suitable organic and cellulose rich substrates, thermo-tolerant microbes, high enzymes stability may support to enhance the biohydrogen production, significantly. Further, various factors which may significantly contribute to enhance biohydrogen production have been discussed thoroughly in reference to the thermophilic biohydrogen production technology. Additionally, existing obstacles such as unfavorable thermophilic biohydrogen pathways, inefficiency of thermophilic microbiomes, genetic modifications, enzymes stability have been discussed in context to the possible limitations of thermophilic biohydrogen production strategy. Structural and functional microbiome analysis, fermentation pathway modifications via genetic engineering and the application of nanotechnology to enhance the thermophilic biohydrogen production have been discussed as the future prospective. Graphical abstract: Image 1 Highlights: Current status of thermophilic biohydrogen production is reviewed using agrowaste. Significance of thermophiles and agrowaste is evaluated in bioH2 production process. Impacts of several operational parameters on bioH2 production are discussed. Existing challenges have been identified and sustainable solutions are recommended. Review focused on potential of waste to energy production at pilot scale.